The Prediction of Prolificacy Using Linear Body Parameters and Craniometric Analysis in Etawah-Grade Does - R. H. Mulyono; C. Sumantri; R. R. Noor; Jakaria Jakaria; D. A. Astuti (Faculty of Animal Science, Bogor Agricultural University, 2018)
Etawah-grade goat is a graded up line between Kacang and Etawah goats, which well adapted to Indonesia’s humid tropical climate. In order to fulfill national meat requirement, it is necessary to increase the population by increasing prolificacy. This study was aimed to determine whether the body and head measurements of the Etawah-grade does can be used as selection criteria for indirect selection of the litter size. The use of does at 3-4 years old (I3 dental condition) from BPTU-HPT Pelaihari and Cordero farms (51 and 55 does, respectively) were based on their specific geographical location characteristics. The body variables were withers height, hip height, body length, chest width, chest depth, thurl width, rump length, chest girth, and cannon circumference, whereas for head variables were acrocranion–prosthion, basion–prosthion, lower jaw length, head height, tuber facial left-right, nasion–rhinion, entorbitale left-right, euryon left-right, supraorbitale left-right. Bergmann methods were applied for measuring the differences of body and head parameters followed by the principal component, Fisher’s discriminant, and principal component regression analyzes. All regression coefficients of linear body measurementss were highly correlated to the litter size (P<0.01), with the equation was Y= 0.015X1b + 0.011X2b + 0.025X3b - 0.002X4b + 0.022X5b + 0.010X6b + 0.022X7b + 0.030X8b + 0.026X9b. The chest girth was the most elastic body size measurement to the litter size. The increasing of 1 cm of doe’s chest girth would result in the increase of litter size, each of 0.0545 and 0.0417 heads born-1 at BPTU-HPT Pelaihari and Cordero farms. Differences in head size and head shape due to the morphometric adaptations cannot be used to predict litter size.